Physical activity in the treatment of metabolic dysfunction-associated steatotic liver disease (MASLD): a review of evidence, mechanisms, and practical clinical recommendations - Wojewódzki, Maciej; Styczyńska, Małgorzata; Cyrzan, Alicja; Zalewski, Jakub; Zysk, Adam; Ząbek, Mateusz; Iwanowska, Martyna; Flis, Beata; Goss, Adrian; Fronczak, Bartosz (Journal of Education, Health and Sport, 2026)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) is common and tightly linked to cardiometabolic risk. Physical activity is recommended, but clinicians need clear guidance on modality, progression, and follow-up. Aim: To summarise exercise evidence in MASLD/NAFLD, outline key mechanisms, and translate findings into practical clinical recommendations. Material and methods: Thematic narrative review. PubMed/MEDLINE, PubMed Central and the Cochrane Library were searched for English- and Polish-language publications from 2005–2025. We included adult structured exercise studies (aerobic, resistance, HIIT, combined), systematic reviews/meta-analyses, guidelines, and methodological papers on liver fat/fibrosis assessment. Outcomes extracted: liver fat (MRI-PDFF/MRS, ultrasound/CAP), ALT/AST, body weight, selected metabolic markers, and non-invasive fibrosis measures (e.g., FIB-4, elastography). Results: Exercise reduces liver fat and yields modest decreases in ALT/AST; improvement may occur without meaningful weight loss. Aerobic and resistance training show similar effects on steatosis, while combined programmes more often improve lipid profile. Short interventions rarely modify non-invasive fibrosis markers, and interpretation is limited by heterogeneous protocols and outcome measures. Conclusions: Exercise should be integrated as standard MASLD therapy alongside comorbidity management and weight-loss strategies when indicated. A practical starting option is progressive moderate-intensity aerobic training plus regular resistance sessions, adapted to comorbidities. Response should be assessed by adherence and routine labs at 8–12 weeks, with quantitative steatosis reassessment at 3–6 months when feasible.